School leader personal traits and teacher work engagement: leadership styles and instructional leadership as mediators - Jaafar, Jamilah; Nik Karimah, Nik Hassan; Idris, Hasbullah; Ssekamanya, Siraje Abdallah (RSIS International, 2025)
A growing number teachers are demotivated and disengaged from their work. This leads to increasing numbers of teachers facing debilitating physical and psychological symptoms such as stress, depression and burnout. Many of them opt to quit prematurely in the form of early retirement. The present study sought to test a hypothesized model of how the personal characteristics of school leaders are related to teacher work engagement through leadership styles and instructional leadership. Data were collected from 198 deputy headteachers and teachers attending a leadership course at the Aminuddin Baki Institute, Genting Highlands, Malaysia. A self-developed instrument based on the survey of literature was used and its validity and reliability assessed. Structural Equation Modeling (SEM) was conducted using Smart PLS software. Results indicated that the measurement instruments enjoyed a high degree of validity and reliability. The proposed structural model of the relationship between school leader personal characteristics and teacher work engagement adequately fit the data. It was found that the direct relationship between school leader personal characteristics and teacher work engagement was not significant. On the other hand, the indirect relationship between school leader personal characteristics and teacher work engagement was significant. Mediation analysis confirmed leadership styles and instructional leadership mediate the relationship between school leader personal characteristics and teacher work engagement. These results are important for the appointment, training, supervision and monitoring of school leaders in Malaysia.